Mass Spectrometric Determination of Bond Energies of High-Temperature Molecules - Karl A. Gingerich (CHIMIA)
The application of the Knudsen cell mass spectrometric method for measuring bond energies of high-temperature molecules is described. Selected recent results are presented and discussed in terms of empirical models of bonding.